ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN DEPRESI PADA ORANG TERKONFIRMASI COVIND-19 DI KABUPATEN PEKALONGAN - Rahajeng Win Martani; Sri Mumpuni Yuniarsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Background : Coronavirus Disease (Covid-19) has become a global pandemic since its emergence in 2019. Data released from COVID Task Force Pekalongan Regency (6/9/2020), the number of patients who were confirmed positive was 115 patients and 22 patients were under treatment. The number of COVID-19 cases that continues to increase will certainly have several impacts on the community, including people who are confirmed to be COVID-19. Patients who are confirmed positive for COVID-19 tend to experience depression. Depression in individuals is influenced by several factors including biological, psychological and social factors.Objective : This study aims to analyze factors associated with depression among people with COVID-19 confirmed in Pekalongan Regency.Method : Thiswas a descriptive correlational research with a cross sectional approach. The population in this study were confirmed COVID-19 patients who were treated in Pekalongan Regency with the sample technique used was total sampling. The instrument used in this study consisted of 4 parts, namely the demographic questionnaire, the Major Depression Inventory (MDI) questionnaire, the Mishel Uncertainty Illness Scale (MUIS) questionnaire, the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire. The analysis used is univariate analysis, bivariate with chi square test.Results :Illness uncertainty was significantly associated with depression among people confirmed eith COVID-19 (p-value < 0.05).Conclusion and reccommendation :The results of the study were expected to be a database for formulating strategies in preventing post-COVID-19 depression. Health workers were expected to be able to reduce illness uncertainty in patients and social support can prevent depression in COVID-19 patients.